Dynamic resource allocation for multimedia services delivery in cellular/infostation integrated HSR networks. (2017) - Lei, Yan; Zhu, Gang; Xu, Shengfeng; Ding, Jianwen; Zhong, Zhangdui
With the rapid development of high-speed railway (HSR) system, the resource allocation problem in HSR wireless network becomes one of the key issues to improve the efficiency of resource utilisation. In this paper, we investigate the downlink resource allocation problem for multimedia services delivery in HSR multiple-input multiple-output (MIMO)-orthogonal frequency division multiplexing (OFDM) system with a cellular/infostation integrated network architecture. Taking the train trajectory and network stability into account, we formulate the problem as a stochastic network optimisation programming, which aims at maximising the overall system utility while keeping the system stable under the total transmission power constraint. To address the NP-hard mixed integer programming, the original problem is firstly transformed into a queue stability problem, and then decomposed into two separate subproblems by the drift-plus-penalty (DPP) approach. Finally, based on the stochastic optimisation technique, a dynamic resource allocation algorithm is proposed and its efficiency is illustrated by theoretical analysis and numerical simulations.